Morphology, Microstructure and Stratigraphy of Some Late Cretaceous Radiolitid Rudists from Jamaica - Simon F. Mitchell (Geologia Croatica, 2003)
Radiolitid rudists from the Upper Maastrichtian of Jamaica include genera Bournonia, Biradiolites and Thyrastylon. Three species of Bournonia are recognised, B. cancellata WHITFIELD, B. barretti TRECHMANN and B. thiadensi VERMUNT. B. cancellata evolves into B. barretti by the acquisition of costae on the anterior side. The species of Bournonia are characterised by a distinctive cardinal apparatus, a thick inner shell layer, and an outer shell layer composed of cellular microstructure. Two species of Biradiolites are recognised – B. rudissimus TRECHMANN has an outer layer composed of cellular microstructure with occasional bands of compact microstructure, particularly in the radial bands, and B. jamaicensis TRECHMANN has a very well organised outer layer with an inner band of cellular microstructure and an outer band of compact microstructure. Biradiolites and Thyrastylon have a similar dentition, a thin inner layer and similar wall structures in the outer layer. Thyrastylon is distinguished from Biradiolites by the infolding of the radial bands in RV and by the presence of oscules in LV. The evolutionary change from Bo. cancellata to Bo. barretti, and the first appearance of Bi. jamaicensis are probably useful biostratigraphic markers of the Upper Maastrichtian.